Singapore joint ventures in China's construction sector - Ng, Hock Sin (2014)
In recent years, Singapore companies have shown much interest investing in China. In fact, Singapore has become China's fifth largest investor in 1994. Hence, the purpose of this report is to analyse Singapore joint ventures in China in the construction sector, highlight the difficulties faced, draw conclusions and make recommendations based on the findings of our research.